Light Bulb Substitute Lens for Measuring Liquid Bias Index - Annisa, Rizki; Hidayah, Husnul; Hartono, Hartono; Supriyadi, Supriyadi (International Journal of Active Learning, 2019)
The purpose of this study is to determine the characteristics of practicum tools developed and prove that the bulb lamp can be used as an innovation replacement of convex lenses, and determine the index of refraction of liquids. This type of research is research and development. The research was conducted at SMK Ma'arif Semarang. The characteristics of the practicum tool are developed as follows: 1) the practicum tool that is created is a form of innovation which utilizes household items such as bulbs that are no longer used; (2) practicum tools can overcome the problems of limitations on marginal schools; (3) The refractive index practicum tool is well designed and practical. The result of feasibility of practicum index of refractive bias obtained percentage of 92,5% with very feasible category. The results of the study showed the refractive index value of water, alcohol and vinegar respectively of 1.8, 1.84 ,; and 1.85. Lamp bulb can be used as a substitute for the convex lens and determine the refractive index of the liquid, but there is a difference between n table with n measured when practicum with a mean of 0.46, this is due to the limitations of practicum tools.